Exploring potential targets for natural product therapy of DN: the role of SUMOylation - Wang, Jingjing; Zhang, Rui; Wu, Chenguang; Wang, Lifan; Liu, Peng; Li, Ping (Frontiers in Pharmacology, 2024)
Diabetic nephropathy (DN) is a common and serious micro-vascular complication of diabetes and a leading cause of end-stage renal disease globally. This disease primarily affects middle-aged and elderly individuals, especially those with a diabetes history of over ten years and poor long-term blood glucose control. Small ubiquitin-related modifiers (SUMOs) are a group of reversible post-translational modifications of proteins that are widely expressed in eukaryotes. SUMO proteins intervene in the progression of DN by modulating various signaling cascades, such as Nrf2-mediated oxidative stress, NF-κB, TGF-β, and MAPK pathways. Recent advancements indicate that natural products regulating SUMOylation hold promise as targets for intervening in DN. In a previous article published in 2022, we reviewed the mechanisms by which SUMOylation intervenes in renal fibrosis and presented a summary of some natural products with therapeutic potential. Therefore, this paper will focus on DN. The aim of this review is to elucidate the mechanism of action of SUMOylation in DN and related natural products with therapeutic potential, thereby summarising the targets and candidate natural products for the treatment of DN through the modulation of SUMOylation, such as ginkgolic acid, ginkgolide B, resveratrol, astragaloside IV, etc., and highlighting that natural product-mediated modulation of SUMOylation is a potential therapeutic strategy for the 3 treatment of DN as a potential therapeutic strategy.